Komunikasi Silang Budaya Sebagai Titik Temu antar Pusat dalam Pusaran Budaya - Bagus Ajy Waskyto Sugiyanto (JOPPAS: Journal of Public Policy and Administration Silampari, 2020)
The purpose of this study was to determine the cross culture as a meeting point between centers in the cultural vortex. The research method in this study uses a descriptive method with a qualitative approach. Culture is an entity that has never been timeless, how could it not even without the culture of the world not materialize. Talking about culture, of course we cannot escape the discussion about friction between cultures. The results of this research, this friction event that makes the emergence of potential conflicts if culture is only understood with tribal and rigid spirit. A process of cross cultural communication is needed to present a dialogue space for each cultural agent. Certainly to produce successful cross-cultural communication requires an awareness of culture in terms of verbs or cultural understanding as a process. It is through this step that cross cultural communication will reach its maximum impact. Keywords: Culture, Cross Cultural Communication